Conceptions of children as subjects of participation in the public policies and programs of Latin America (Encuentros, 2022)
This article is derived from the doctoral thesis project Participation as experience, a view from the subjectivities of Boys and Girls. The approach seeks to contribute to the construction of other ways of conceiving the participation of children in the different polyphonic and multiform ways to recognize their own political subjectivity, and offer a general and reflective normative panorama from history, starting from a approach to the participation of children in the construction of their own identity as social and political subjects in Latin America. Within this revision from a normative perspective, special emphasis is placed on public policies on childhood, adolescence and youth that have been consolidated in Latin America. Likewise, the places and not places where the children are found in the contexts and how it is visualized are shown, as well as other topics such as experiences, participation and social construction. It can be affirmed that boys and girls in modern countries and societies have been conceived as citizens who must be under the tutelage of norms and laws; from the perspectives of participation and political subjectivity in the framework of the states that respect the condition of children with democratic and legal guarantees. Finally, it reflects on some of the problematic questions associated with the traditional hegemonic figure, which positions children in permanent places of subalternation.
Keywords: Boys and girls, political subjectivity, political participation, identity.